Frustrated Lewis pair catalyst realizes efficient green diesel production - De-Chang Li; Zhengyi Pan; Zhengbin Tian; Qian Zhang; Xiaohui Deng; Heqing Jiang; Guang-Hui Wang (Nature Communications, 2024)
Abstract Hydrotreating renewable oils over sulfided metal catalysts is commercially applied to produce green diesel, but it requires a continuous sulfur replenishment to maintain catalyst activity, which inevitably results in sulfur contamination and increases production costs. We report a robust P-doped NiAl-oxide catalyst with frustrated Lewis pairs (i.e., P atom bonded with the O atom acts as an electron donor, while the spatially separated Ni atom acts as an electron acceptor) that allows efficient green diesel production without sulfur replenishment. The catalyst runs more than 500 h at a weight hourly space velocity (WHSV) of 28.3 h−1 without deactivation (methyl laurate as a model compound), and is able to completely convert a real feedstock of soybean oil to diesel-range hydrocarbons with selectivity >90% during 500 h of operation. This work is expected to open up a new avenue for designing non-sulfur catalysts that can make the green diesel production greener.